A case for developing normative bereavement suport through the SPHE curriculum in Irish primary and post-primary schools - Mc Guckin, Conor; Lynam, Aoife (Hibernia College Dublin, 2018)
Throughout the school-age years (approximately 4 to 18 years of age), young people are faced with various crises that can significantly affect development and normative task fulfilment; bereavement is one such crisis. Physical and psychosocial crises such as bereavement intensify throughout the developmental process and present complex concerns for educators. Researchers agree that young people are often seen as the ‘forgotten mourners’ in a family unit (Packman et al., 2006; Wender, 2012) and that support from ‘one good adult’ can be a significant positive factor in the mental well-being of young people (Dooley and Fitzgerald, 2012). Findings from research states that teachers play a vital role in recognising the child’s grief as well as aiding the psychosocial well-being of pupils in their care (Donnelly, 2001). While the psychological pain and processes of grief are mostly unavoidable, the behaviour of adults towards pupils who are bereaved is a major contributory factor towards what is often referred to as a healthy progress through grief (Cranwell, 2007). In Ireland, 43% of nine years olds have experienced the death of someone important to them (for example, a parent, a sibling, a grandparent or a close friend; Williams et al., 2009). However, there is an evidential gap in the empirical findings in relation to how young people are supported in the Irish school environment following bereavement (Holland, 2008; McGovern and Barry, 2010; McGovern and Tracey, 2010; Rowling and Holland, 2000; Tracey and Holland, 2008). This chapter explores the potential role of Social, Personal, and Health Education (SPHE) as a curricular area for providing bereavement support to pupils to understand their grief experience. Pedagogically, teachers do not need to be experts in bereavement counselling in order to support a pupil who is grieving but they should be aware of how to respond appropriately and use the curricular areas to support and guide pupils in their classroom. As pupils spend one third of their lives in school, the reactions of teachers and their peers to a significant bereavement in their lives are important, as is the role of the school in ensuring that the needs of those who are bereaved are recognised and responded to in an appropriate manner. The curricular area of SPHE provides ample opportunity for the issue of death to be discussed but teachers in the current research have expressed a lack of training and guidance in the area, which has resulted in an avoidance of the topic in the classroom. This chapter provides an overview of findings from research in relation to how SPHE is currently being utilised for grief support in the teaching profession and the classroom. Qualitative data was collected from: (a) interviews with representatives (n = 7) from organisations with expertise in bereavement support, and (b) focus groups (n = 10) with primary and post-primary teachers to explore their views about how bereavement is currently tackled in the classroom.
Voices of educators in 21st century Ireland
PUBLISHED
Dublin, Ireland
Keywords: Bereavement in children; Bereavement in school children; Schools and bereavement; Inclusive Society; EDUCATION; Children; Education